Ekspektasi Umat Buddha Mengenai Teknik Ceramah Dhamma (Dhammadesana) Oleh Dhammadūta Di Vihara Di Jakarta Barat - Madiyono Madiyono (Jurnal Ilmiah Kampus: Sati Sampajanna, 2020)
Delivering Dhamma using interesting strategies and accordance with  expectations of the lay-people is an important skill for Dhammadūta. However, in fact, some of the Dhammadūta did not pay attention to the needs of listener during their  Dhammadesana. Therefore, this research was carried out, with the aim of knowing the expectations of Buddhists regarding the strategies to deliver Dhamma by Dhammadūta.This research is a descriptive quantitative study by survey method. The data were obtained by distributing questionnaires to Buddhists at 3 monasteries in West Jakarta. The data were then processed using descriptive statistics.Based on the results of data processing, it is concluded that, in relation to the timing of the  Dhammadesana, based on lay-people expectations ideally all session is carried out within a period of 60 to 90 minutes. The most ideal time to deliver  Dhammadesana material that people able to focus on paying attention is within a period of 30 to 60 minutes. It prefer the material is about 60 minutes long and is carried out in the morning, in the morning chanting session. Interesting topics of the  Dhammadesana materials are about daily life refer to  the Tipitaka Scripture. The study will be meaningful when it is presented lightly and accompanied by a joke. They hope, the  Dhammadesana can encourage them to practice the Dhamma better. Regarding the strategy of delivering the  Dhammadesana, it will be effective when the speaker delivers the material at a moderate tempo, not too slow or quick, using  technological media, such as video combined with Power Point media. The  Dhammadesana material is more interesting and easier to understand when the speaker can present it with  a joke. It is better using legal Indonesian language supported by good body language.  Some of hand movements when doing elaboration of Dhamma can help to strengthen people's belief and understanding of the presentedmaterial better. The material is better delivered using a voice with  moderate volume.It gets stronger when the speaker makes eye-contact with the lay-people as listeners during  Dhammadesana activities. Regarding the attitude of the Dhammadūta, the  most favored position when delivering the  Dhammadesana material is sitting on the chair that has been provided with a smiley expression. In general, Buddhist lay-people in Cengkareng West Jakarta consider that the best Dhammadūta are those who are humble, authoritative, and have a sense of humor.